(untitled) (Bioscience Journal, 2020)
Paracetamol (PCM) overdose can cause hepatotoxicity with oxidative stress; the present study was carried out to establish the possible protective effect of olive leaves extract (OLE) on toxicity induced by paracetamol in adult male rats. Twenty four adult male rats were divided into four equal groups; control, olive leaves extract group, paracetamol group and olive leaves extract plus paracetamol group. Some biochemical parameters and liver histopathology were evaluated. PCM treatment significantly increased serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), total bilirubin, gamma-glutamyltransferase (GGT), lactate dehydrogenase (LDH), urea, creatinine and alpha-fetoprotein. Paracetamol was found to significantly increase malonaldehyde (MDA) and decrease glutathione reductase (GR) activity in tissue and significantly decrease total antioxidant capacity (TAC) and superoxide dismutase (SOD) in serum. Administration of OLE caused a significant decrease serum AST, ALT enzyme, total bilirubin, GGT, LDH, creatinine, urea, alpha-fetoprotein. Also, amelioration of oxidant – antioxidant status with olive leaves extract was observed in addition to a significant decrease in MDA and a significant increase in TAC in liver tissue with a significant increase in glutathione reductase (GR) and SOD in serum compared to paracetamol treated group The chemical pathological changes were in step with histopathological observation suggesting marked hepatoprotective result of olive leaves extract. It could be concluded that olive leaves extract (OLE) treatment may be effective in decreasing hepatic injury and oxidative stress induced by paracetamol overdose in male albino rats.